A self-healing electrocatalytic system via electrohydrodynamics induced evolution in liquid metal - Yifeng Hou; Fengyan Wang; Chichu Qin; Shining Wu; Mengyang Cao; Pengkun Yang; Lu Huang; Yingpeng Wu (Nature Communications, 2022)
Self-healing electrodes may offer opportunities to prevent catalyst deterioration during electrocatalytic reactions. Here the authors demonstrate a self-healing system by exploiting electrohydrodynamics induced evolution of Bi in liquid metal and apply this to CO2 electroreduction to formate.